A Strategy to Modulate the Bending Coupled Microwave Magnetism in Nanoscale Epitaxial Lithium Ferrite for Flexible Spintronic Devices. Issue 12 (6th November 2018) - Shen, Lvkang; Lan, Guohua; Lu, Lu; Ma, Chunrui; Cao, Cuimei; Jiang, Changjun; Fu, Huarui; You, Caiyin; Lu, Xiaoli; Yang, Yaodong; Chen, Lang; Liu, Ming; et al.
Abstract: With the development of flexible electronics, the mechanical flexibility of functional materials is becoming one of the most important factors that needs to be considered in materials selection. Recently, flexible epitaxial nanoscale magnetic materials have attracted increasing attention for flexible spintronics. However, the knowledge of the bending coupled dynamic magnetic properties is poor when integrating the materials in flexible devices, which calls for further quantitative analysis. Herein, a series of epitaxial LiFe5 O8 (LFO) nanostructures are produced as research models, whose dynamic magnetic properties are characterized by ferromagnetic resonance (FMR) measurements. LFO films with different crystalline orientations are discussed to determine the influence from magnetocrystalline anisotropy. Moreover, LFO nanopillar arrays are grown on flexible substrates to reveal the contribution from the nanoscale morphology. It reveals that the bending tunability of the FMR spectra highly depends on the demagnetization field energy of the sample, which is decided by the magnetism and the shape factor in the nanostructure. Following this result, LFO film with high bending tunability of microwave magnetic properties, and LFO nanopillar arrays with stable properties under bending are obtained. This work shows guiding significances for the design of future flexible tunable/stable microwave magnetic devices. Abstract : Nanoscale flexible lithium ferrite with bending tunable/stable ferromagnetic resonance is fabricated. The bending tunability of the resonance field highly depends on the magnetic anisotropy of materials and can be predicted by simulations. The results provide guiding significances for the design of future bending tunable/stable microwave magnetic devices.